2019
DOI: 10.1038/s41590-019-0467-1
|View full text |Cite
|
Sign up to set email alerts
|

IL-1R3 blockade broadly attenuates the functions of six members of the IL-1 family, revealing their contribution to models of disease

Abstract: IL-1R3 is the co-receptor in three signaling pathways that involve six cytokines of the IL-1 family (IL-1α, IL-1β, IL-33, IL-36α, IL-36β and IL-36γ). In many diseases, multiple cytokines contribute to disease pathogenesis. For example, in asthma, both IL-33 and IL-1 are of major importance, as are IL-36 and IL-1 in psoriasis. We developed a blocking monoclonal antibody (mAb) to human IL-1R3 (MAB-hR3) and demonstrate here that this antibody specifically inhibits signaling via IL-1, IL-33 and IL-36 in vitro. Als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 55 publications
5
65
0
Order By: Relevance
“…The present study identified IL‐36α as a robust and early marker for kidney damage induced by increased phosphate excretion per nephron. IL‐36α is a recently identified pro‐inflammatory cytokine that belongs to the IL‐1 family and reported to contribute to the pathophysiology of several disorders associated with inflammation, including psoriasis, chronic obstructive pulmonary disease, and obesity [10,11]. Like other cytokines, IL‐36α is expressed primarily in immuno‐competent cells, but is induced in renal tubular cells in patients and rodent models with AKI and CKD [9,12].…”
Section: Discussionmentioning
confidence: 99%
“…The present study identified IL‐36α as a robust and early marker for kidney damage induced by increased phosphate excretion per nephron. IL‐36α is a recently identified pro‐inflammatory cytokine that belongs to the IL‐1 family and reported to contribute to the pathophysiology of several disorders associated with inflammation, including psoriasis, chronic obstructive pulmonary disease, and obesity [10,11]. Like other cytokines, IL‐36α is expressed primarily in immuno‐competent cells, but is induced in renal tubular cells in patients and rodent models with AKI and CKD [9,12].…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin-1 R3 is the co-receptor in three signaling pathways that involve six cytokines of the IL-1 family (IL-1α, IL-1β, IL-33, IL-36α, IL-36β, and IL-36γ). In vivo (animal models) targeting IL-1R3 significantly attenuated heterogeneous cytokine-driven inflammation and disease severity 58…”
Section: Understanding Better the Mechanisms Currently Targeted Withmentioning
confidence: 99%
“…Lastly, IL1RAP (also named IL-1R3) blockade, using mAb81.2 and mAb3F8, which induces antibody-dependent cellular cytotoxicity and IL-1 signaling blockade in AML and CML cells provides evidence that IL1RAP may be a potent target in AML cells ( 33 , 193 ). All functions of the IL-1 family (IL-1α, IL-1β, IL-33, IL-36α, IL-36β, and IL-36γ) are attenuated by IL1RAP blockade with the human IL1RAP antibody, MAB-hR3 ( 194 ). No increase in IL-6 production was observed, and IL1RAP blockade induced a broader anti-inflammatory activity than that associated with IL-1R1 blockade by IL-1Ra antagonist anakinra.…”
Section: Therapies In Developmentmentioning
confidence: 99%